Punjab Heritage News (2008)
[Dt.:] Auf dieser Seite finden sich Nachrichten zum kulturellen und architektonischen Erbe des Panjab. Der Fokus liegt vor allem auf sikhistischen Stätten, berichtet wird aber auch über andere religiöse und nichtreligiöse Gebäude. Der gesamte Panjab, also sowohl der pakistanische wie auch der indische Teil wird hier behandelt. - [Engl.:] This page features regularly updated news about the architectural and cultural heritage of the Panjab. The focus is chiefly on Sikh religious sites but news is also provided about religious buildings of other groups and secular architecture. The whole Panjab, which means the pakistani as well as the indian part is referred to here